Meningkatkan Daya Ingat Hafalan Siswa Melalui Metode Bernyanyi Pada Pembelajaran Tematik di SDN 3 Sukaratu - Raisa Ajmiliatinnisa Hilman; Fajar Nugraha; Hatma Heris Mahendra (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This research was motivated by the low memory of student for remembering the lesson because the use of less varied method in class 2 of 3 sukaratu elementary school in Tasikmalaya. This study aims to identify and describe the planning, implementation, and skill improvement of studen’s memory in thematic learnign by using singing learning method. The method used in this research is Classroom Action Research (PTK) according to Kemmis and Mc. Taggart which consists of planning, action, observation, and reflection in each cycle. The discussion of this study uses using singing learning method In the learning process of time unit and capital letters which are testedat the end of each cycle The results of the study stated that singing learning method were able to improve memory of student in 3 Sukaratu of elementary school. This increase before using singing learning method (pre-action) obtained an average value of 63,54 with a percentage of 19,31% in the "less" category. After using that singing learning method in cycle I, an average value of 69,67 was obtained with a percentage of 51,62 % in the "less" category. Then in cycle II an average value of 81.77 was obtained with a percentage of 87.10 % in the "very good" category.